Disfunção Arterial como Possível Mecanismo de Agressão Cardíaca em Pacientes com Diabetes Mellitus Tipo II. Estudo Doppler-Ecocardiográfico - Matsubara, Beatriz Bojikian [UNESP]; Okoshi, Katashi [UNESP]; Okoshi, Marina Politi [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Pimenta, Walkyria P. [UNESP]; Christovan, José C. [UNESP]; Padovani, Carlos R. [UNESP]; Cicogna, Antonio Carlos [UNESP] (My University, 1997)
Purpose - To evaluate the left ventricular structure and function and the arterial stiffness in type II diabetic patients. Methods - Thirteen diabetic patients, men and women (age 55±8 years) were included in the study. None of the patients had any other clinical disorders. Doppler-echocardiography and non-invasive monitoring of arterial blood pressure were performed. All the results were compared to an age and sex matched control group (n=12). Results - There were no differences between the groups for diastolic blood pressure, dimensions of cardiac chambers and ventricular systolic and diastolic function indexes. Diabetic patients had increased left ventricular mass index (101±10 vs 80±14g/m 2; p<0.001) and increased arterial stiffness(0.86±0.26vs0.69±0.19mmHg/mL;p<0.05),when compared to control group. Conclusion - Diabetes mellitus is associated to increased systemic arterial stiffness and this may contribute to the adverse effects of diabetes on left ventricular morphology.
Arterial Dysfunction as a Possible Mechanism of Cardiac Injury in Type II Diabetic Patients. A Doppler-Echocardiographic Study
Keywords: Arterial hypertension; Myocardial mass; Systemic arterial stiffness